FRI0030 Anti-TNF-α Antibody Targeted To Inflamed Synovial Tissue for The Treatment of Rheumatoid Arthritis. (15th July 2016) - Colombo, F.; Sblattero, D.; De Maso, L.; Durigutto, P.; Biffi, S.; Belmonte, B.; Tripodo, C.; Meroni, P.L.; Tedesco, F.; Macor, P.
Abstract : Background: TNF-α neutralizing molecules represent one of the most efficient therapeutic approaches to control inflammation in rheumatoid arthritis (RA). The widespread distribution in the body induces the inhibition of TNF-α in all the tissues, requesting the use of high dose of this expensive drug. Another problem that has not yet been solved in the management of RA patients is how to reduce and possibly avoid the side effects, particularly the increased risk of common and opportunistic infections, which may be associated with long-term administration of these therapeutic drugs. Objectives: The aim of the present investigation was to show that a recombinant protein obtained by fusing a synovial targeting peptide to an anti-TNF-α neutralizing antibody has a distinctive homing property for inflamed synovium and is effective in controlling joint inflammation in experimental models of arthritis. Methods: The modified anti-TNF-α antibody specific for the synovial tissue (MC13) was generated by cloning the sequence for a synovial homing peptide (CKSTHDRLC) downstream of the cDNA for the variable regions of anti- TNF-α antibody adalimumab in the context of a miniantibody (scFv-Hinge-CH2-CH3 domains). Immunofluorescence technique was used to initially assess the ability of fluorescent-MC13 to target only inflamed synovial tissue. The biodistribution and the efficacy of the treatment with MC13 were evaluated in a rat model of antigen-induced arthritis (AIA). Results: In vitro studies have shown that adalimumab and MC13 maintain the ability to neutralize human TNF-α and bind to rat and mouse TNF-α. Based on these findings, we used a rat model of arthritis to evaluate their in vivo therapeutic effect. The ability of MC13 to selectively target inflamed synovial tissues was evaluated by immunofluorescence analysis. A rat model of antigen-induced mono-arthritis was used to analyse the in vivo distribution of MC13 labelled with the near-infrared probe cyanine 5.5 using time-domain near infrared optical imaging. The results showed that the labeled-MC13 preferentially localized in the inflamed synovium with a peak at 4 days and persisted for more than 3 weeks, while failing to bind to healthy synovial tissue. MC13 was able to prevent inflammation in the rat model of antigen-induced arthritis, as evaluated by the measurement of joint swelling, the count of PMN number and the level of IL6 in synovial tissue and the histologic assessment of tissue damage. Intravenous injection of MC13 prevents acute inflammation in all the animals while the same dose of adalimumab was almost ineffective. MC13, administred i.v. 4 days after arthritis induction, was also able to cure joints analysed 7 days after the induction of inflammation. Conclusions: Our results demonstrated that MC13 can selectively target inflamed and abrogate the inflammation in a model of antigen-induced arthritis with no sign of toxicity. Disclosure of Interest: None declared